Ulàpeitök methodology: bribri wisdom, and practices for conducting research - Sylvester, Olivia (2026)
This article presents the results of more than fifteen years of collaboration between a Bribri author and a non-Indigenous co-author, focused on the application of ancestral Bribri principles in academic research. Its aim is to analyze both the achievements and the challenges of an intercultural collaboration grounded in the Bribri principle of ulàpeitök, which promotes mutual respect and reciprocity. The article describes community-based methods such as s-kṍpàkö, which differ from Western and colonial research approaches. The analysis is situated within broader debates on epistemicide, decolonization, and Indigenous research methodologies. It highlights how research that does not emerge from autonomous epistemological frameworks, and that fails to address structural racism, can perpetuate harm for Indigenous peoples. Finally, the article reflects on the need to recognize and value Indigenous methodologies within academia and offers recommendations for researchers and institutions.